Developing Effective E-Learning Modules for Adult Education - Santoso, Ekbal; Hossam, Ahmed; Abdallah, Mona (Journal International Inspire Education Technology, 2025)
The demand for flexible and accessible education has led to the increasing adoption of e-learning in adult education. Traditional learning models often fail to accommodate the diverse needs of adult learners, who require self-paced, interactive, and practical learning experiences. Effective e-learning modules must incorporate pedagogical strategies that enhance engagement, knowledge retention, and skill application. This study aims to develop and evaluate e-learning modules tailored to adult learners by assessing their effectiveness in improving learning outcomes, motivation, and user experience. A mixed-methods research approach was employed, combining learner performance assessments, user feedback surveys, and instructor interviews. Findings indicate that interactive content, adaptive learning pathways, and real-time feedback significantly enhance adult learner engagement and comprehension. Statistical analysis revealed a strong correlation between structured e-learning design and improved knowledge retention. The study concludes that well-designed e-learning modules contribute to effective adult education by promoting autonomous learning and practical skill development. Future research should explore the long-term impact of e-learning on professional growth and strategies for optimizing digital learning environments for diverse adult learner populations.